Implementasi Supervisi Akademik UNTUK MENINGKATKAN KOMPETENSI GURU DI SMP Negeri 1 Rembang KABUPATEN PURBALINGGA - Eka Budi Setyawan; Noor Miyono; Ngurah Ayu Nyoman Murniati (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2021)
Academic supervision by the principal is a necessity in order to maintain the quality of education in the school. One school that according to the researchers has a good quality of education is SMP N 1 Rembang Purbalingga. The aims of the study are describe and analyze: planning, implementation, evaluation and follow-up of evaluation results, constraints and impacts of academic supervision.This study uses a qualitative method with a phenomenological approach. Data collection techniques include interviews, observation and documentation. Meanwhile, data analysis is carried out through the process of data reduction, data presentation and conclusion drawing.The results of this study can be concluded as follows: 1) The academic supervision plans are cooperative, creative, comprehensive, flexible and sustainable, 2) Implementation of online academic supervision activities due to the Covid-19 pandemic. Academic supervision can overcome the difficulties of teachers in carrying out the learning process, 3) Evaluation of the results of academic supervision is conveyed directly, personally and followed up by the teacher by improving learning. Schools make an effort to improve pedagogical competence through peer tutors, education and training, guidance and IHT, 4) there are no problems in the implementation of academic supervision, and 5) The implementation of academic supervision can improve teacher pedagogical competence, especially in the use of learning media and understanding the character of students.In order to be more optimal, according to teacher researchers, they should be more proactive and responsive with academic supervision activities in their schools.